1995
DOI: 10.1097/00004714-199508001-00004
|View full text |Cite
|
Sign up to set email alerts
|

Moclobemide and Tricyclic Antidepressants in Severe Depression

Abstract: There is no generally accepted definition of severe depression, but hospitalization, high scores on rating scales, and the presence of psychotic symptoms are widely considered to be indicators of severe cases. For the purpose of this analysis of the antidepressant efficacy of the reversible inhibitor of monoamine oxidase A moclobemide, all hospitalized cases were selected from the current database of comparative studies and compared with the standard tricyclics imipramine and clomipramine. The cases from compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…It is also possible that the optimal dose of MOC for treatment of more severe or refractory mood disorders is higher than currently appreciated. For example, Angst et al (1995) have marshalled data to suggest that MOC at doses of р400 mg/day is a less effective treatment of severely depressed inpatients than either clomipramine (у150 mg/day) or MOC at higher dosages (у450 mg/day). It would appear, then, that prescription of larger doses (i.e., 450 to 900 mg/day) would be a rational first step for management of an ineffective but well-tolerated trial of MOC.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the optimal dose of MOC for treatment of more severe or refractory mood disorders is higher than currently appreciated. For example, Angst et al (1995) have marshalled data to suggest that MOC at doses of р400 mg/day is a less effective treatment of severely depressed inpatients than either clomipramine (у150 mg/day) or MOC at higher dosages (у450 mg/day). It would appear, then, that prescription of larger doses (i.e., 450 to 900 mg/day) would be a rational first step for management of an ineffective but well-tolerated trial of MOC.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of clinical studies demonstrated that moclobemide (300 mg -600 mg) was superior to placebo and thereby efficaceous in the treatment of the major depressive episodes (Bonnet, 2003). A meta-analysis of results from clinical studies comparing the effect of moclobemide with imipramine failed to reveal any difference in efficacy between moclobemide and imipramine in any subgroup of hospitalized depressives, including patients in the highest HAM-D severity band and psychotic patients (Angst, Amrein, & Stabl, 1995). When compared to clomipramine (25 -200 mg; tricyclic antidepressant (TCA)) moclobemide was generally better tolerated but showed mixed effects with respect to efficacy.…”
Section: Depressionmentioning
confidence: 99%
“…This case also serves to illustrate how different pharmacology can help ensure a satisfactory clinical outcome in treatment-resistant MDD patients. Because of the incompatibility of MOC with other antidepressants, the treatment combinations with MOC are usually limited [2]. In this case, however, this combination not only inhibited MAO-A, but also caused broad receptor activity, especially of MT 1 and MT 2 receptors, which is one possible explanation for positive clinical effect.…”
Section: Discussionmentioning
confidence: 87%
“…The long-term followup studies lasting 6-12 months have also demonstrated that the antidepressant efficacy of MOC is maintained. Higher doses of MOC (> 450 mg/day) may be more effective in severe depression, while a lower dose tends to 1 3 cause a weaker response than tricyclic antidepressants [2]. MOC is well tolerated by most patients.…”
Section: Introductionmentioning
confidence: 97%